Discours volontaristes et effets réels. La situation de l’occitan - Fabrice Bernissan (Lengas)
We showed in a recent article that Occitan has about 100 000 speakers. Its use will greatly reduce in the coming decades, even if actions are taken to revitalize this language. The analysis of the situation shows that these actions are little concerted, poorly calibrated and never evaluated. We shall show that institutional language policies, largely insufficient and ill-suited, do not allow the continuation of Occitan. The actors are little coordinated and do not know how to use the major advantage of this language: its native speakers. We conclude by making a series of proposals in the direction of the short-term development of Occitan.